The geographical dimensions of water expansion in the District of Kalar - مهدى, د. محمد مهدى کریم; قاسم, آ.د. ابراهیم قاسم درویش محمد (Sulaimani Journal for Humanities, 2025)
Settlement has always been regarded as the most important human phenomenon. Therefore, the research entitled (Geographical Dimentions of Settlement footprint expansion in Kalar district) tried to show the expansion of prosperity traces in the study area. The research; Through remote sensing techniques, it has tried to draw a map of the expansion of prosperity in half a century of geography of Kalari district. Aerial images of the study area (1983-2023) were taken over five periods (decades) and analyzed through Descriptive and quantity methodology. It was found that there was a significant expansion in the area of settlements, which was 9.3 km2 in the base year of the study, but increased to 49.3 km2 in the target year and spread to unused land. Although the expansion of prosperity indicates the vitality and development of the region, it has had negative consequences on the environment, climate and agricultural land.
Keywords: Settlement footprints; settlement expansion; Kalar district; settlement geography